2019
DOI: 10.1097/htr.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Reality Interventions for Improvement of Neurocognitive Performance After Traumatic Brain Injury: A Systematic Review

Abstract: VR interventions hold significant potential for improving neurocognitive performance in patients with TBI. While there is some evidence for translation of gains to activities of daily living, further studies are required to confirm the validity of cognitive measures and reliable translation to real-life performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…These findings likely extend to the doubts expressed by participants relating to the use of VR by people with cognitive impairments or mental health conditions. These were seen as potentially exclusionary criteria to clients engaging with VR, despite prior research that has used VR to successfully treat psychological symptoms in people with anxiety [26], and cognitive impairments in people with dementia [5] and TBI [6]. These existing studies indicate that cognitive impairments and mental health can be improved through VR, and therefore are not necessarily factors which would limit engagement in VR-based rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings likely extend to the doubts expressed by participants relating to the use of VR by people with cognitive impairments or mental health conditions. These were seen as potentially exclusionary criteria to clients engaging with VR, despite prior research that has used VR to successfully treat psychological symptoms in people with anxiety [26], and cognitive impairments in people with dementia [5] and TBI [6]. These existing studies indicate that cognitive impairments and mental health can be improved through VR, and therefore are not necessarily factors which would limit engagement in VR-based rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of virtual reality (VR) technology is advancing rapidly in many areas of healthcare and rehabilitation [1,2]. In both physical [2][3][4] and cognitive [5,6] rehabilitation, researchers have used virtual games and experiences to engage people with a variety of health conditions in novel and motivating therapies. Intervention studies have targeted physical impairments, activity limitations, and participation restrictions in people with a range of diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence demonstrates that cognitive rehabilitation (CR), through previously learned skills or new compensatory strategies, is effective in patients with TBI as it enhances cognitive and psychosocial interaction [812]. In recent years, technological innovations have allowed the development of new rehabilitative strategies, such as PC-based rehabilitation or Virtual Reality Training (VRT), which have proven effective in the CR of neurological patients [1316]. Chen et al [17], examining the efficacy of PC-based rehabilitation in TBI subjects, observed significant posttreatment improvements on cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that PC cognitive training can be a potential CR strategy to optimize cognitive and global functional recovery [18, 19]. Several studies using VR have shown that it increases cognitive and behavioral skills in patients with TBI [1316]. Indeed, it has been demonstrated that VR may be effective in improving executive functions in patients with TBI in the subacute phase [20].…”
Section: Introductionmentioning
confidence: 99%